Risk and reliability analysis : a handbook for civil and environmental engineers - Singh, V. P. (Vijay P.) (American Society of Civil Engineers, 2007)
"The consideration of the risk involved in any situation, project, or plan becomes an integral part of the decision-making process. Risk and Reliability Analysis: A Handbook for Civil and Environmental Engineers presents key concepts of risk and reliability that apply to a wide array of problems in civil and environmental engineering."--Jacket.